Effect of Ad-libitum, split and restricted feeding on performance, digestibility and welfare of broiler chicken (2017)
An experiment was conducted to assess the performance, welfare and digestibility of broilers fed varying forms of feeding regimes. The objective of this work research was investigate the possibility of improving growth performances, digestibility and welfare of broilers using ad libitum, split and restricted feeding. Formulated diet was given in four different forms Ad-libitum (Treatment 1) twice a day meal/split feeding (Treatment 2) thrice a day feeding (Treatment 3) 3 hours restriction feeding (Treatment 4). Experimental design was completely randomized design. 240 broilers were randomly allotted to four treatments with 6 replicates and 10 birds per replicate. Birds were weighed weekly to evaluate their performances, faeces was collected on day 42, to determine digestibility and rectal temperature was taken as a measure of bird's wellbeing. Results showed that there were no significant differences (p≥ 0.05) in performance of birds across treatments but values from birds fed Ad-libitum were higher. Rectal temperature (RT) differ at week 4, birds fed 3 hours restricted feeding had the highest RT (41.62°C) while the least RT were from birds fed Ad-libitum (41.20°C). Significant differences were obtained in digestibility and nutrient utilization of broilers with respect to feeding regimes. Crude protein (CP) digestibility was significantly higher in birds fed 3 hours restriction (81.91%) while birds fed Ad-libitum had the least (46.76%). The digestibility of crude fibre was higher in birds fed 3 hours restricted feeding regime (86.77%) the least was from birds fed thrice a day feeding regime (62.66%). A similar trend was obtained for digestibility of gross energy. Ad-libitum feeding had the highest non-significant performance values but split feeding optimized feed and nutrient utilization thereby enhancing performance and minimizing nutrient waste at the same time.